Measuring Parental Control and Its Relationship to Cognitive Abilities of Early-Grade Students - Ekaterina Lanina; Aleksandra Bochaver; Inna Antipkina (Voprosy obrazovaniya / Educational Studies Moscow, 2021)
The article presents a tool for assessing the parental regulation of children’s behavior at the start of the school. The questionnaire assesses the implementation by parents of two typical control functions (direct control of the child’s behavior and communicative mediation between the child and the environment), as well as a poorly studied construct — parental control over digital devices (“gadgets”) that the child uses. It was demonstrated that the severity of parental control is sensitive to the characteristics of parents (higher education, age, number of children in the family) and the characteristics of the child (cognitive achievements at the start of the school).